1968
DOI: 10.2355/tetsutohagane1955.54.4_534
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Oxide Layers of Steels

Abstract: The scales formed on the steels are examined through the electron probe microanalysis. Examined steels are low carbon rimmed steel, silicon killed steel, weather-resistance steel, high strength steel, sulfer free-cutting steel, ferritic and austenitic stainless steels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…The black layer near the surface was composed of hematite and magnetite, and the following gray layer composed of wüstite. It should be noted that wüstite is dissociated 11,13) into magnetite and Fe below 843 K. 12) EPMA analysis shows that the black angular particles in the gray layer of Fig. 2 represent magnetite.…”
Section: Oxidation Of Iron Samplesmentioning
confidence: 99%
“…The black layer near the surface was composed of hematite and magnetite, and the following gray layer composed of wüstite. It should be noted that wüstite is dissociated 11,13) into magnetite and Fe below 843 K. 12) EPMA analysis shows that the black angular particles in the gray layer of Fig. 2 represent magnetite.…”
Section: Oxidation Of Iron Samplesmentioning
confidence: 99%
“…..... (2) ........ (3) Precipitation of magnetite results in the first stage with the formation of a meta-stable iron-rich Fe 1-y O. Then, transformation of the iron-rich Fe 1-y O to magnetite and metal iron proceeds in the second stage.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, incubation time of 100 s and more was required to start the reaction. 2,6,9,10,12,13) Isothermal transformation temperature and possibly the prior scaling temperature affected the incubation time. Transformation of a bulk FeO (free from the base metal) was studied by Chaudron and his coworkers at below 843 K. [4][5][6] They indicated that the rate of transformation had a maximum at 753 K (480°C), 4) and the liberated iron dissolved in the remaining FeO and increased its lattice constant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, numerous efforts have been made to control the composition of the non-metallic inclusions in molten steel [1][2][3][4][5][6] and the morphology of inclusions in solid phase steel. [7][8][9][10][11] The behavior of non-metallic inclusions in solid phase steel has been investigated mainly for Si-killed steel. Ohshiro et al reported that control of the composition of the inclusions to make them easily deformable during hot rolling was effective in improving the reliability of high fatigue spring steel.…”
Section: Introductionmentioning
confidence: 99%